Animal model of continuous peritoneal lavage with vacuum peritoneostomy - Rodrigues,Adilson Costa (2017)
Abstract Purpose: To establish and evaluate the feasibility of continuous peritoneal lavage with vacuum peritoneostomy in an animal model. Methods: Eight pigs aged 3-4 months, females, were anesthetized and submitted to laparotomy and installation of a continuous peritoneal lavage with vacuum peritoneostomy. The sta-bility of the system, the physiological effects of washing with NaCl 0.9% and the sys-tem clearance were evaluated. Results: Stability of vacuum peritoneostomy was observed, with no catheter leaks or obstructions and the clearance proved adequate, however, the mean volume of fluids aspirated by the peritoneostomy at the end of the experiment was higher than the volume infused by the catheters (p=0.02). Besides that, the animals presented a progressive increase in heart rate (p=0.04) and serum potassium (p=0.02). Conclusion: The continuous peritoneal lavage technique with vacuum peritoneostomy is feasible and presents adequate clearance.